The role of indirect interactions in structuring tropical insect communities - Morris, R; Lewis, O (2002)
Apparent competition is a form of indirect interaction among species that can potentially structure biological communities. In insect communities, parasitoid-mediated apparent competition has been proposed as a particularly important structuring force. We argue that short-term apparent competition may be less important in structuring insect communities in tropical regions, compared with temperate regions. This prediction arises because, compared with temperate insects, tropical insects that share natural enemies are more likely to be isolated in both space and time.